2017
DOI: 10.5152/eurjrheum.2017.16113
|View full text |Cite
|
Sign up to set email alerts
|

Late ventricular potentials in familial Mediterranean fever with and without AA amyloidosis

Abstract: Data on increased rhythm and conduction disturbances in FMF are limited and conflicting. For instance, Akcay et al. (13) found that QT dispersion (QTd) and corrected dispersion (QTcd), which reflect cardiac repolarization heterogeneity and thereby suggest predisposition for cardiac arrhythmias, are increased in uncomplicated FMF. However, different methodologies have yielded normal QTd results in both uncomplicated and amyloidosis-affected FMF patients (14, 15). Limited information is found on depolarization-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Furthermore, OP plasma levels were positively correlated with VS in patients with coronary disease but not in young subjects without clinical symptoms or risk factors of atherosclerosis [43, 44]. Interestingly, OP levels could be reduced by statins and angiotensin II blockade [45]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, OP plasma levels were positively correlated with VS in patients with coronary disease but not in young subjects without clinical symptoms or risk factors of atherosclerosis [43, 44]. Interestingly, OP levels could be reduced by statins and angiotensin II blockade [45]. …”
Section: Discussionmentioning
confidence: 99%
“…While FMFrelated pericarditis and cardiac amyloidosis are the most commonly expected complications, recent studies have reported that FMF patients can suffer sudden cardiac death or malign arrhythmias that are caused by cardiac repolarization abnormalities, even without the presence of amyloidosis. [4,5] This has been linked to the chronic inflammation occurring in FMF. It is believed that the chronic inflammation observed in FMF can lead to endothelial injury and ischemic cardiovascular damage.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] There are many studies in the literature which have used these new indices that indicate ventricular repolarization in FMF. [4,5,[14][15][16] Studies have revealed that the Tp-e interval is superior to QT dispersion in foreseeing sudden cardiac death and ventricular arrhythmia. [17] Our aim in this study was to evaluate the longstanding as well as the newly developed electrocardiogram parameters indicating myocardial repolarization and to assess the QT interval, corrected QT interval, Tp-e interval, corrected Tp-e, Tp-e/corrected QT, P wave dispersion to see whether pediatric patients diagnosed with FMF have a predisposition toward arrhythmia.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, its prevalence in Turkey is estimated to be one in 1,000 children. Mediterranean fever (MEFV) gene [1][2][3] mutation is thought to be responsible for its occurrence.…”
Section: Introductionmentioning
confidence: 99%